1976
DOI: 10.7164/antibiotics.29.65
|View full text |Cite
|
Sign up to set email alerts
|

Orally active 7-phenylglycyl cephalosporins. Structure-activity studies related to cefatrizine (SK&F 60771).

Abstract: The synthesis of a series of related broad-spectrum 7-phenylglycyl cephalosporins with 3-heterocyclicthiomethyl substituents is described. The effects of benzene-ring hydroxylation and 3-substituent variation on the in vitro antibacterial activity, height and duration of mouse serum levels, and effectiveness in protecting against bacterial infection in the mouse are examined. Included for comparison are cephalexin, cephaloglycin and their ortho-, meta-and para-hydroxy derivatives. The biological properties exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Cefatrizine is a 7-phenyl-glycyl semi synthetic cephalosporin with a thiomethylic heterocyclic substituent in position 3 of the 7-am inocephalosporanic acid nu cleus [1], Cefatrizine has the following chemical structure: 7-[F(-)-2-amino-2-(phydroxyphenyl)acetam ide -] -3 -( 1H -1,2,3 triazole -4(5) -ylthiomethyl) -3 -cephem -4-carboxylic acid (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cefatrizine is a 7-phenyl-glycyl semi synthetic cephalosporin with a thiomethylic heterocyclic substituent in position 3 of the 7-am inocephalosporanic acid nu cleus [1], Cefatrizine has the following chemical structure: 7-[F(-)-2-amino-2-(phydroxyphenyl)acetam ide -] -3 -( 1H -1,2,3 triazole -4(5) -ylthiomethyl) -3 -cephem -4-carboxylic acid (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…11 Specifically, Adibi and Soleimanpour12 demonstrated that the Michaelis constant of glycylglycine is 43.4 mM, whereas the bulkier dipeptide, glycylleucine, has a K, value equal to 26.8 mM in perfused human jejunum. Similarly, Dunn et al 13 reported that the absorption site was even more discriminating to structural differences with para substitution of a hydroxyl group on the 7-phenylglycyl cephalosporins, resulting in a significant increase in absorption over the metu-substituted compound in the mouse.…”
Section: ~_ _ _~_ _ _ _~ _____-mentioning
confidence: 99%
“…In our research for suitable synthetic methods of monoamides, we found that two carbonyl chloride groups of 2 are selectively hydrolyzed by treatment with water at 1040°C to give a novel diimidazopyrazine derivative (3). Since both carbonyl imidazolide moieties in 3 are activated, the compound (3) reacts effectively with two equivalent moles of amines to produce the corresponding monoamides.…”
Section: Chemistrymentioning
confidence: 99%
“…Nucleophilic displacement of the C-3 acetoxy group of 6 and 8 with the appropriate heterocyclic thiols and pyridine derivatives was achieved in the usual manner. 3,4,5) The prepared C-3 analogs (9-13) are presented in Table 1.…”
Section: Chemistrymentioning
confidence: 99%